Disiplin Kerja Aparatur Di Kantor Dewan Perwakilan Rakyat Daerah Kota Palu - Tinggogoy, Filo Leonardo; Amane, Ade Putra Ode; Syugiarto, Syugiarto (Jurnal ADMINISTRATOR, 2024)
The purpose of this research is to determine the work discipline of officials in the Palu City Regional People's Representative Council Office. The informants in this research were officials from the Palu City Regional People's Representative Council. Apart from that, to find out the Work Discipline of State Civil Apparatus, other informants, namely Staff. This research data consists of primary data and secondary data obtained directly through field research (interviews). Data was analyzed using the results of interviews with the City Regional People's Representative Council office. Palu, namely Secretary, Head of General Affairs, Head of Civil Service and Administration Sub-Division, Staff. The results of the research show that to find out the work discipline of the apparatus in the Palu City Regional People's Representative Council office, in carrying out their duties and functions in government administration at the Palu City Regional People's Representative Council office, the author chose a theory that is considered more suitable to be applied to government organizations, in this case the Council Office Palu City Regional People's Representatives, if carried out simultaneously will create State Civil Apparatus Work Discipline, which is Alfred R. Lateiner's theory (In Soejono 1983: 72) namely Time Discipline, Discipline Regulations and Dress, Discipline, Work Responsibilities. The author concludes that the disciplinary policy of state civil servants in the Palu City Regional People's Representative Council Office.  assessed from the three indicators/dimensions, which are considered to be well implemented Time Discipline and Dress Code Discipline while the indicators/dimensions of Responsibility Discipline whose results are still not implemented well